Bentuk Komunikasi Antar Umat Beragama dalam Menciptakan Kerukunan di Desa Pembakulan Kecamatan Batang Alai Timur Kabupaten Hulu Sungai Tengah - Nasruddin Nasruddin (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2023)
Indonesia is currently faced with a plurality of religions, and of course, this plurality of religions is very vulnerable to conflict between religious communities. One area that has a plurality in the religious field is Pembakulan Village. Pembakulan Village is one of the villages that inhabits the Mount Meratus area which is very far away with modern civilization and adheres to several religions such as Christianity, Hinduism, Islam and one of them is the local religion, namely Kaharingan. Of course there are interesting which made them able to survive and live in harmony until now. And one of the factors that create harmony is good communication and a high sense of tolerance. Therefore, the purpose of this research is to find out how the forms of communication and forms of tolerance between religious communities in Pembakulan Village are to create harmony. Based on the results of interviews and observations of researchers, this article argues that there are two forms of communication that create harmony in Pembakulan Village, Batang Alai Timur District, Hulu Sungai Tengah Regency, namely interpersonal and group and forms of tolerance, namely cooperation, mutual openness, freedom of religion and respect for religious activities.